Sulfasalazine Inhibits Inflammation and Fibrogenesis in Pancreas via NF-κB Signaling Pathway in Rats with Oxidative Stress-Induced Pancreatic Injury [Retraction] - Wang Y; Tian F; Yan M; Fan J; Wang L; Kuang R; Li Y (Dove Medical Press, 2022)
Wang Y, Tian F, Yan M, et al. Drug Des Devel Ther. 2016;10:1743–1751. At the authors request, the Editor and Publisher of Drug Design, Development and Therapy wish to retract the published article. Previous concerns had been raised to the authors regarding the alleged duplication of images in Figures 1A-b and 1A-c and a corrigendum had been published. More recently, concerns have also been raised to the authors regarding the alleged duplication of images between Figure 2A-b and 2A-e. In addition, there were also concerns raised regarding the duplication of certain features between several images from Figures 2 and 3. The journal wishes to recognize that these particular concerns were introduced during the publication process and were not introduced by the authors. However, in relation to the duplication of images between Figure 2A-b and 2A-e, the authors have acknowledged this. The authors were able to provide original data to the journal, but it was unable to support the integrity of the research and the authors requested to retract the article and the Editor agreed with this. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.